Implemetasi Model Pembelajaran Kolaboratif Melalui Program Kampus Mengajar Angkatan 6 Di SMPN 5 Tanggul - Adhisa Nur Aini; Astri Widyaruli Anggraeni (Jurnal Masyarakat Mengabdi Nusantara, 2024)
The Teaching Campus is one of the Merdeka Belajar Kampus Merdeka (MBKM) programs which aims to be a learning platform that provides opportunities for students throughout Indonesia to study outside campus for one semester to practice their skills and explore the interests and talents they already have. This research aims to implement a collaborative learning model through the Class 6 Teaching Campus program at SMPN 5 Tanggul. The collaborative learning model is implemented with the aim of increasing interaction between students and developing critical thinking and collaboration skills. The research method used is a qualitative method with a case study approach through observation, interviews and documentation. Thus, it can be concluded that the implementation of the collaborative learning model through the Class 6 Teaching Campus program at SMPN 5 Tanggul can be an effective alternative in improving the quality of learning in secondary schools. This research contributes to the development of collaborative learning methods and provides recommendations for related parties to continue and develop this program further.